KEEFEKTIFAN PENGGUNAAN MODEL INVESTIGASI KELOMPOK DAN MODEL BERMAIN PERAN UNTUK MENINGKATKAN KEMAMPUAN BERPIDATO IMPROMPTU PESERTA DIDIK SMA YANG INTROVER DAN EKSTROVER (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study (1) determine the effectiveness of the use of the model in the investigation of a group of students improve impromptu speech, (2) determine the effectiveness of the use of the model plays a role in improving students' speaking impromptu, and (3) determine the effectiveness of the model and model investigation group play role to enhance the ability of learners impromptu speech. This study type quasi experimental study. This research was conducted to compare the two models between model investigations with the model group play to improve high school students' impromptu speech class XI are introverted and extroverted, the source of research data Sacred Spirit High School students of the school year 2011/2012, as well as personality expert (psychologist). Data were collected through observation, questionnaires, interviews, tests, and journals and analyzed qualitative and quantitative description. Results of this study was to determine the effectiveness of the learning model to improve speech. The results of the study, the model plays a role more effectively spent on impromptu speech until proven earned value above KKM. Students get excited and interested in following an impromptu speech learning lessons